Media Business Development in the Context of Global Digitalization - Viktor P. Kirilenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
In the context of global changes in the media market under the influence of Internet technologies, it becomes necessary to identify the main trends of its development, so the characteristic of the market trends, the integration process of entrepreneurial structures in the media industry, aimed at increasing their competitiveness at the present stage of development of the market economy. In the context of an ever-changing, competitive digital ecosystem and against the background of General cuts in advertising budgets in the print press, radio, and television, advertising investments in the digital environment are increasing starting in 2019. Revenues of legacy news media organizations (also called old or traditional media organizations) are constantly declining due to the high degree of audience participation in new media due to the use of user-generated content, media automation, and new digital media organizations. Using mathematical-statistical and logical research methods, the article identifies specific features of the media business sphere, which include audience fragmentation, culture of creative destruction, and hypercompetition in the media market. In addition, key issues and current changes in the media industry in the context of global digitalization are highlighted, reflecting the introduction of innovative technologies that affect the media industry, and the decline in traditional methods of delivery and media consumption. Global digitalization has affected the growth of media platforms, resulting in an increase in the supply of content itself, as well as significant changes in its consumption by the advertising market.